Pharmacological evaluation of novel (6-aminopyridin-3-yl)(4-(pyridin-2-yl)piperazin-1-yl) methanone derivatives as TRPV4 antagonists for the treatment of pain. Issue 7 (1st April 2017) - Tsuno, Naoki; Yukimasa, Akira; Yoshida, Osamu; Suzuki, Shinji; Nakai, Hiromi; Ogawa, Tomoyuki; Fujiu, Motohiro; Takaya, Kenji; Nozu, Azusa; Yamaguchi, Hiroki; Matsuda, Hidetoshi; Funaki, Satoko; et al.
Graphical abstract: Abstract: A novel series of (6-aminopyridin-3-yl)(4-(pyridin-2-yl)piperazin-1-yl) methanone derivatives were identified as selective transient receptor potential vanilloid 4 (TRPV4) channel antagonist and showed analgesic effect in Freund's Complete Adjuvant (FCA) induced mechanical hyperalgesia model in guinea pig and rat. Modification of right part based on the compound16d which was disclosed in our previous communication led to the identification of compound26i as a flagship compound. In this paper, we described the details about design, synthesis and structure-activity relationship (SAR) analysis at right and left part of these derivatives (Fig. 1 ).